China's growing international competitiveness and its implications for Japanese firms. - Li, Zhanke. (2008)
The purpose of this study is to investigate the evolving structure of the exports of China and Japan in the US and EU markets in order to provide a comprehensive overview of China's improving international competitiveness and to make inferences about its possible implications for Japanese industry.